2002
DOI: 10.1097/00005537-200208000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Undifferentiated Carcinoma: The Search for a Better Outcome

Abstract: For patients with good performance status and limited intracranial or intraorbital disease, we continue to advocate initial chemoradiotherapy followed by craniofacial resection. Patients who are deemed inoperable as a result of advanced disease may nevertheless experience significant palliation with chemoradiotherapy only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
119
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 11 publications
6
119
0
6
Order By: Relevance
“…[8][9][10] Orbital involvement, skull base invasion and intracranial extension have been reported in 20-25 per cent of patients. 8,11 In the present series, 25 per cent of patients had intracranial extension, while 19 per cent had intra-orbital extension. Involvement of these critical structures poses a great challenge to achieving complete resection (R0, i.e.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…[8][9][10] Orbital involvement, skull base invasion and intracranial extension have been reported in 20-25 per cent of patients. 8,11 In the present series, 25 per cent of patients had intracranial extension, while 19 per cent had intra-orbital extension. Involvement of these critical structures poses a great challenge to achieving complete resection (R0, i.e.…”
Section: Discussionsupporting
confidence: 40%
“…TNM = tumournode-metastasis; 3D = three-dimensional; 5-FU = 5-fluoro-uracil; RT = radiotherapy sinonasal undifferentiated carcinoma with pre-operative radiochemotherapy comprising pre-operative RT (50-54 Gy) and three cycles of cyclophosphamide, doxorubicin plus vincristine chemotherapy. 11 Surgery was performed within 1 month of radiochemotherapy. The authors reported a two-year overall survival rate of 47 per cent for all evaluable patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, current series show an overall survival between 40 and 75% [11][12][13][14]. Neck metastases in advanced local disease is a poor prognostic sign [8].…”
Section: Discussionmentioning
confidence: 95%
“…Invasive growth can lead to manifestations such as proptosis, cranial nerve palsies and visual disturbances. In spite of the frequent locally advanced disease at presentation, at this time only 5-13% of patients have nodal metastasis [8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Inspite of these multimodality treatment these tumour recur in one year and most of these patient died. [10]. So early diagnosis and prompt treatment can improve the survival of these patient.…”
Section: Discussionmentioning
confidence: 99%